Knockout Gene-Based Evidence for PIWI-Interacting RNA Pathway in Mammals - Li, Yinuo; Zhang, Yue; Liu, Mingxi (Frontiers in Cell and Developmental Biology, 2021)
The PIWI-interacting RNA (piRNA) pathway mainly consists of evolutionarily conserved protein factors. Intriguingly, many mutations of piRNA-pathway factors lead to meiotic arrest during spermatogenesis. The majority of piRNA factor knockout animals show arrested meiosis in spermatogenesis, and only a few show post-meiosis male germ cell arrest. It is still unclear whether the majority of piRNA factors expressed in spermatids are involved in long interspersed nuclear element-1 repression after meiosis, but future conditional knock-out research is expected to resolve this. In addition, recent hamster knockout studies showed that a piRNA factor is necessary for oocytes, in complete contrast to the findings in mice. This species discrepancy allows researchers to re-examine the function of piRNA in female germ cells. This mini-review focuses on the current knowledge of protein factors derived from mammalian knockout studies and summarizes their roles in the biogenesis and function of piRNAs.